Hyperspectral microscopy imaging based on Fourier ptychographic microscopy. (1st May 2022) - Zhang, Peiwei; Zhao, Jufeng; Lin, Binbin; Wu, Xiaohui; Cui, Guangmang
Abstract: Hyperspectral resolution, high spatial resolution, and a wide field of view (FOV) are the targets of optical spectral microscopy imaging. However, hyperspectral microscopy imaging technology cannot provide a wide FOV and a high spatial resolution at the same time. Fourier ptychographic microscopy (FPM) is a novel microscopy imaging technique that uses LEDs at varying angles to capture a series of low-spatial-resolution images that are used to recover images that have both high spatial resolution and a wide FOV. Since FPM cannot obtain the spectral resolution of the sample, in this paper, an efficient strategy based on the FPM system is proposed for the reconstruction of hyperspectral images. First, the traditional FPM setup is optimized, with a new experimental setup based on halogen lamp illumination and a narrow band-pass filter to capture a series of low-spatial-resolution images at different wavelengths. Second, a new algorithm, combining hyperspectral resolution imaging using interpolation compensation and a phase retrieval algorithm, is proposed to reconstruct high-spatial-resolution, wide FOV, and hyperspectral resolution images. Finally, we verified the feasibility and effectiveness of our experimental setup and algorithm by both simulation and experiment. The results show that our method can not only reconstruct high-spatial-resolution and wide FOV images, but also has a spectral resolution of 5 nm.